Serum cystatin C levels are associated with coronary artery calcification in women without chronic kidney disease. Issue 6 (December 2017) - Sugiyama, Hiroyasu; Miyoshi, Toru; Osawa, Kazuhiro; Miki, Takashi; Koide, Yuji; Nakamura, Kazufumi; Morita, Hiroshi; Ito, Hiroshi
Abstract: Background: Chronic renal disease (CKD) is a determinant of coronary artery calcification (CAC), which is a predictor of cardiovascular events. However, in a population without CKD, the association between CAC and renal function is unclear. CAC is affected by sex. This study aimed to determine whether serum cystatin C, a sensitive marker of kidney function, or sex differences are associated with CAC in patients without CKD. Methods: We evaluated 456 consecutive patients (61 ± 13 years, 42% women) without CKD and evidence of coronary artery disease. The CAC (Agatston) score was examined by multidetector computed tomography. Results: When patients were categorized into three CAC groups based on the Agatston score, mild (<10), moderate (11–399), and severe (≥400) in each sex, serum cystatin C levels gradually increased by severity of CAC in women, but not men. Receiver operating characteristic curve analysis showed that, in women, a cut-off value of 0.97 mg/l for cystatin C discriminated patients with severe CAC with a sensitivity of 71% and specificity of 77% (area under the curve, 0.74; 95% CI: 0.62–0.86; p < 0.01). Multivariate logistic analysis showed that serum cystatin C was not associated with severe CAC in all patients and men, but this association was observed in women (OR: 7.80 for cystatin C ≥ 0.97 mg/l, 95% CI: 1.76–34.6, p < 0.01). Conclusion: Higher serum cystatin C levels are associated with greater CAC in women without CKD. Measurement of cystatin C may be useful for identifying women who are at high risk for cardiovascular disease.